Prevalence of Fetal Alcohol Spectrum Disorders in 4 US Communities. Issue 7 (July 2018) - May, Philip A.; Chambers, Christina D.; Kalberg, Wendy O.; Zellner, Jennifer; Feldman, Haruna; Buckley, David; Kopald, David; Hasken, Julie M.; Xu, Ronghui; Honerkamp-Smith, Gordon; Taras, Howard; Manning, Melanie A.; et al.
Abstract : (Abstracted from JAMA 2018;319(5):474–482) Several single-site, active-case ascertainment studies in the United States have shown widely varying prevalence estimates for fetal alcohol spectrum disorders, composed of fetal alcohol syndrome, partial fetal alcohol syndrome, and alcohol-related neurodevelopmental disorder. Prevalence of fetal alcohol spectrum disorders are challenging to estimate using routine surveillance methods, and cases are often misdiagnosed or undiagnosed.